Extraction of organic analytes from foods a manual of methods - Self, Ron (Royal Society of Chemistry, 2005)
This book is designed as a laboratory manual of methods used for the preparation and extraction of organic chemical compounds from food sources. It offers ideas on how to facilitate progress towards the total automation of the assay, as well as proposing assays for unknowns by comparison with known methods. Beginning with an introduction to extraction methodology, Extraction of Organic Analytes from Foods then progresses through sample preparation, extraction techniques (partition, solvation, distillation, adsorption and diffusion) and applications. Subject indices for the applications are organised by commodity, method, chemical class and analyte, and provide useful examples of references from the literature to illustrate historical development of the techniques. Examples of methods that have been compared, combined or used in collaborative trials have been correlated and used to form the beginnings of a database that can be expanded and updated to provide a laboratory reference source. Logically structured and with numerous examples, Extraction of Organic Analytes from Foods will be invaluable to practising food analysts as both a reference and training guide. In addition, the introductory sections in each chapter have been written with food science and technology students in mind, making this an important title for academic libraries.
Keywords: Food -- Analysis.; Food -- Composition.; Organic compounds.; elektronické knihy; electronic books